Study influence factors of the spraying process on the properties of electric arc spraying coatings - Ageev, M.; Solovuch, E.; Lopata, V.; Burlachenko, O.; Vihilianska, N. (Problems of Tribology, 2021)
The paper considers possibilities to increase the wear resistance, corrosion resistance, and service life for parts machines and mechanisms via their hardening and renovating using electric arc coatings characterized by high density, adhesion strength, and micro hardness thanks to activation of the spraying process. Also, the possibility of controlling the properties of restored surfaces owing to choice of the related equipment with required structure and characteristics in order to prolong the service life of machinery parts is shown. The right choice of equipment for spraying makes it possible to increase the speed and temperature of the spraying gas and particles, reduce the droplet diameter, increase the density and reduce the oxidation of coatings. The influence of spray factors such as the flow rate and pressure of working gases, composition of combustion mixture, spraying distance, dispersion of the spray, properties of wire material, etc. on the properties of the coatings obtained has been investigated. The possibility of controlling the properties of surfaces owing to choice with required characteristics electric arc coatings is shown. The influence of spray factors such as the flow rate and pressure of working gases, composition of combustion mixture, spraying distance, dispersion of the spray, properties of wire material, etc. on the properties of the coatings obtained has been investigated. The use of coatings makes it possible to increase the wear and corrosion resistance of working surfaces of machine parts and mechanisms, in particular ship parts, and so to reduce the costs of alloyed steels and alloys. The coatings application is associated with implementation of a fundamentally new approach, according to which the strength and carrying capacity of a part is provided by its basic material, whereas the resistance to corrosion, wear, and other factors may be increased via using hardening protective coatings. There are many alternative methods for producing coatings, from which it is advisable to choose an optimal, easy to implement, and inexpensive one. Of the variety of methods for hardening coating deposition, the most common technologies used to restore and improve the performance properties of parts are gas-thermal spraying techniques, among which the cheapest and simplest method is electric arc spraying (EAS), whose current improvement is aimed at modifying and activating the spraying process. Such combined technologies do not require additional expensive equipment and operations, which predetermines a reduction in the cost of hardening processes.